Proterozoic cooling and exhumation of the northern central Halls Creek Orogen, Western Australia: constraints from a reconnaissance 40Ar/39Ar study - Bodorkos, S.; Reddy, Steven (2004)
The Palaeoproterozoic Halls Creek Orogen preserves the most complete record of Barramundi (1880 1820 Ma) tectonism in northern Australia, but appears unaffected by the 1750 1500 Ma tectonomagmatic activity that pervades other parts of the North Australian Craton. However, reliable geochronological data in the Halls Creek Orogen are largely restricted to U Pb zircon and monazite determinations, and the history of post tectonic cooling in the crystalline basement remains poorly understood. A reconnaissance 40Ar/39Ar study has been undertaken in the northern central part of the orogen, where 1850 1845 Ma high grade metamorphism pre dated 1835 1825 Ma emplacement of the Mabel Downs Tonalite, and the subsequent development of the Highway Shear Zone under greenschist facies conditions. Hornblende and biotite 40Ar/39Ar results from the Mabel Downs Tonalite yield plateau ages of 1705 5 Ma and 1546 19 Ma, respectively, interpreted to record cooling through the temperatures 540 40C and 315 45C, respectively. These values yield slow time averaged cooling rates of 1.5 0.5C/106 years (1845 1705 Ma) and 1.4 0.4C/106 years (1705 1545 Ma). Variably discordant muscovite and biotite 40Ar/39Ar analyses from sheared leucogneiss and retrogressed pelitic migmatite in the Highway Shear Zone are difficult to interpret, although none record Palaeoproterozoic isotopic closure and most preserve evidence for resetting during Neoproterozoic (900 800 Ma) recrystallisation. In the absence of a reliable minimum age for the Yampi Orogeny (previously published pre 1000 Ma K ;Ar ages may be affected by unrecognised excess argon), the present 40Ar/39Ar data may reflect deformation associated with reactivation of the Highway Shear Zone during this event.